Business Plan of Ecofriends Sdn Bhd / Zul Ihsan Md Desa - Md Desa, Zul Ihsan (2002)
This business plan is prepare by the management of ECOFRIENDS SDN BHD (353019-U) for new entrepreneurs and businessman who wish to venture in this type of business. It emphasizes on the type of service offered by the company, its strengths, and the potential for the company to develop and grow. ECOFRIENDS takes great pride in providing cleaning services for chemical and petrochemical plants by utilizing the high-pressure water blasting method, which is considered new to the indutry but is highly demanded by factories and such plants. ECOFRIENDS are also provides of high-pressure bolt tensioning for machines and plants, with the cooperation of an established principal provider in the United Kingdom. We projected a gross profit of at least RM 1.2 million for the year 2001 with possible contracts offered and sealed with majors dealers such as Petronas Refinery Sdn. Bhd, Eastman Chemicals Sdn. Bhd, Huntsman Tioxide Sdn Bhd, Polyethelene (Malaysia) Sdn. Bhd and Esso Gas (Malaysia) Sdn Bhd. As to date, ECOFRIENDS has engaged into various projects and contracts with the listed companies and has achieved acknowledgements due to the quality service provided. The costs of execution of such projects are roughly estimated in abot RM 0.75 million, and with the suitable machineries and equipment,along with our highly skilled and professional core personnel, ECOFRIENDS SDN BHD are sure to secure more contracts and bring about a much better profit for the coming year. The management team of ECOFRIENDS SDN BHD wishes to thank the parties involved in making this project a success and their cooperation are very much appreciated, we look forward in working with the said parties again in the future.